PERFORMANCE OF GROWTH AND YIELD CAYENNE PEPPER (Capsicum frutescens L.) WITH DOSAGE OF NPK AND MONOSODIUM GLUTAMATE (MSG) FERTILIZER - Maryana, Maryana; Sumarwoto, Sumarwoto; Sipangkar, Silvana Delima (Universitas Pembangunan Nasional Veteran Yogayakarta, 2022)
The demand for cayenne pepper always increases every year along with the increase in population. To increase the yield of cayenne pepper, among others, through fertilization by giving doses of NPK and monosodium glutamate (MSG) fertilizers. The purpose of the study was to determine the best dose of NPK and MSG fertilizer on the growth and yield of cayenne pepper plants. The research was carried out at the Practical Garden of the Faculty of Agriculture, UPN